2000
DOI: 10.1037/0893-164x.14.4.367
|View full text |Cite
|
Sign up to set email alerts
|

Assessing variation in alcohol outcome expectancies across environmental context: An examination of the situational-specificity hypothesis.

Abstract: Using an in vivo manipulation, this study examined whether alcohol outcome expectancies (AOEs) vary across environmental settings. Two hundred twenty-one undergraduates were randomly assigned to 1 of 4 conditions in which environmental context (an on-campus bar vs. a laboratory) and instructed phase of intoxication ("just enough to begin to feel intoxicated" vs. "too much to drink") were manipulated. AOEs were assessed with a revised version of the Effects of Alcohol Scale (L. Southwick, C. Steele, A. Marlatt,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
81
4
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(102 citation statements)
references
References 41 publications
(74 reference statements)
15
81
4
2
Order By: Relevance
“…At a methodological level, our results suggest that when adequate precautions are taken, an expectancy effect of alcohol on aggression can be found. This is consistent with the situation-specificity hypothesis (Wall, McKee, Hinson, 2000;Wall, Hinson & McKee, 2001). …”
Section: Accepted Manuscriptsupporting
confidence: 80%
“…At a methodological level, our results suggest that when adequate precautions are taken, an expectancy effect of alcohol on aggression can be found. This is consistent with the situation-specificity hypothesis (Wall, McKee, Hinson, 2000;Wall, Hinson & McKee, 2001). …”
Section: Accepted Manuscriptsupporting
confidence: 80%
“…This method, while important in presenting a potentially more naturalistic exposure to proximal cues, essentially creates a compound stimulus that prevents examination of the independent contribution of the distal cues. One such combined cue study was conducted by Wall, McKee, and Hinson (2000). The authors examined the impact of environmental setting (bar vs. laboratory) on college students' alcohol outcome expectancies.…”
mentioning
confidence: 99%
“…Important issues are whether and in what contexts such alcohol associations are likely to be activated. Initial research with explicit measures of alcohol-related associations suggests that positive outcome expectancies are activated in alcohol-related contexts (Wall et al, 2000(Wall et al, , 2001, but only one study has been conducted with an implicit measure (Stacy et al, 1994). Stacy et al (1994) found that, compared with participants who read a vignette in which alcohol was absent, participants who read a vignette in which alcohol was present were more likely to endorse alcohol-related behaviors in an outcome association task (i.e., writing the fi rst behavior that comes to mind after seeing an outcome prime, such as "feeling more relaxed").…”
mentioning
confidence: 99%